Persepsi Kualitas Hidup Penderita HIV Positif di Kota Semarang (Universitas Negeri Semarang, 2020)
HIV is still considered as a terrible, hard to be cured and even deadly disease by the society.This research is a qualitative research which focuses on the perception of the PLWH’s quality of life in the Semarang city. Initial informant determined with purposive sampling techniques and to complete the further information, snowball sampling technique is used. The method used in the data collection is in-depth interviews with key informant that is 5 gay patients with positive HIV in the Semarang city and triangulation informants including families of PLWH, health workers providing services, Semarang City KPA, and Peer Assistant Coordinator.The result showed that PLWH’s perception regarding to their quality of life is good and satisfying. This is because PLWH in this study understand HIV very well, regularly take ARVs, maintain a healthy lifestyle, attend the Peer Support Group, and get support from the family or friend.To continously improve the quality of PLWH’s life, program makers are advised to give counseling and health education towards the community about HIV so that the society will not have a misleading knowledge about HIV and they can participate in the prevention of HIV transmission as well as to the risky groups to continously carry out routine HIV test and prevent the transmission of HIV.